The Demand for Youth: Explaining Age Differences in the Volatility of Hours - Jaimovich, Nir; Pruitt, Seth; Siu, Henry E (American Economic Review, 2013)
Over the business cycle young workers experience much greater volatility of hours worked than prime-aged workers. This can arise from age differences in labor supply or labor demand characteristics. To distinguish between these, we document that, for young workers, both the cyclical volatilities of hours and wages are greater than those of the prime-aged. We argue that a general class of models featuring only age-specific labor supply differences cannot reconcile these facts. We then show that a simple model featuring labor demand differences can. (JEL E32, J13, J22, J23, J31)